Food attitudes of nutrition students at the university of Pernambuco - Sena Barroso, Laudicéia; Felipe dos Santos Silva, Diego; Cinthia Ferro Cavalcante, Taisy; Marques Sotero, Andréa; Sobral Silveira, Matheus; Vantini Checchio Skrapec, Michele (Seven Editora, 2023)
Eating attitudes are defined as beliefs, thoughts, feelings, behaviors, and relationships to food. Nutrition students have particular eating attitudes towards food, being also influenced by their academic background and the environment in which they live, reflecting on their professional practices. This study aimed to analyze the eating attitudes of Nutrition students at the University of Pernambuco Campus Petrolina. This is a cross-sectional study with nutrition students, over 18 years of age, of both genders, who were invited to optionally answer a structured electronic questionnaire. The mean score for eating attitudes was 57.98 (8.43) points. When comparing the eating attitudes and subscales scores between independent variables, women had higher scores compared to men in the total scale 58,7 (DP=8,5) and in relationship with food 18,4 (DP=2,5) and concerns about food and weight gain 6,9 (DP=2,62) subscales. Overweight individuals scored higher on the total scale 62,9 (DP=9,2) and in concerns about food and weight, 7,8 (DP=2,9) and in the restrictive and compensatory practices, 5,4 (DP=2,1), subscales. Participants showed little dysfunctional eating attitudes. Overweight women and individuals, in general, had worse eating attitudes. It is important and necessary to have academic training in nutrition with a greater appreciation of the humanities disciplines so that students have a broader view of health care with a biopsychosocial approach and a critical view. DOI: https://doi.org/10.56238/devopinterscie-182